2014
DOI: 10.1007/s11104-014-2131-8
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural uses of plant biostimulants

Abstract: Background Plant biostimulants are diverse substances and microorganisms used to enhance plant growth. The global market for biostimulants is projected to increase 12 % per year and reach over $2,200 million by 2018. Despite the growing use of biostimulants in agriculture, many in the scientific community consider biostimulants to be lacking peer-reviewed scientific evaluation. Scope This article describes the emerging definitions of biostimulants and reviews the literature on five categories of biostimulants:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
1,111
3
95

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,658 publications
(1,387 citation statements)
references
References 326 publications
45
1,111
3
95
Order By: Relevance
“…There is a body of evidence of positive effects of these products that are reproduced in laboratory as well as under field conditions (Arancon et al, 2012;Zandonadi et al, 2013;Calvo et al, 2014). Humic substances from vermicompost enhance ATP hydrolysis activity, protein abundance, proton extrusion Zandonadi et al, 2010), and messenger ribonucleic acid (mRNA) levels (Quaggiotti et al, 2004) of the PM H + -ATPases in a way similar to that previously described for the plant hormone, auxin (Frías et al, 1996).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…There is a body of evidence of positive effects of these products that are reproduced in laboratory as well as under field conditions (Arancon et al, 2012;Zandonadi et al, 2013;Calvo et al, 2014). Humic substances from vermicompost enhance ATP hydrolysis activity, protein abundance, proton extrusion Zandonadi et al, 2010), and messenger ribonucleic acid (mRNA) levels (Quaggiotti et al, 2004) of the PM H + -ATPases in a way similar to that previously described for the plant hormone, auxin (Frías et al, 1996).…”
Section: Discussionmentioning
confidence: 73%
“…The term "auximones" was coined to designate organic extracts from peat able to promote plant growth. A hundred years later, several products have been identified as biostimulants, although still lacking proper scientific evaluation, and only proved to work under controlled conditions (for a review see Calvo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Also it have been reported that an application effect of this substances is the production of phytohormones which promotes the growing (Smolen et al, 2014), all this due to the capacity of this substances to generate soil aggregates, proteins, carbohydrates, aliphatic biopolymers and lignin content, thus favoring the microbial activity, improving soil structure and the development of several beneficial microorganism (Calvo et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The substance correspond to microorganisms, humic acids, fulvic acids, hydrolyzed proteins, amino acids and algae (Calvo et al, 2014); the application of these substances has been converted into an important strategy for agriculture sustainability, since its properly use allow the combination of either pesticides and/or fertilizers of chemical synthesis without decreasing the crops yield (Cordovilla et al, 1999;Aseri et al, 2008;Ambrosini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation